Práticas de arquitetura para demandas populares: a experiência dos arquitetos da família - Priscila Silva Nogueira (2010)
This dissertation presents the adoption of a different architectural practice to attend popular demands. The usual architectural procedure is inefficient to attend them due to the social distance between popular clients and architects. Therefore, a criticism to the conventional architectural practice is constructed based on the argentine architect Rodolfo Livingstons method of designing, called El Metodo. His procedure was studied and applyed to real clients and continuouslydiscussed and modified. In order to ensure the research development, advertisements were used to attract clients and a group of architects was formed to attend them. Throughout the research, some specificissues became prominent as they lead to possible changes in the procedure of Livingston. Ways of communication, the agents role, the dichotomy between the manual and the intellectual work and the scales of working do not just reveal architectural practices complexities and contradictions but also suggest other possibilities.